Nepal's Leasehold Forestry for the Poor - Some Learnings about Unintended Consequences - Baral, Jagadish C.; Thapa, Yam Bahadur (Banko Janakari, 2017)
Abstract on the PDF Banko Janakari Vol.13(2) 2003: 46-53